The classical and alternative pathways of complement activation play distinct roles in spontaneous C3 fragment deposition and membrane attack complex (MAC) formation on human B lymphocytes - Leslie, Robert Graham Quinton (Blackwell Science Inc, 2004)
The contributions of the classical (CP) and alternative (AP) pathways of complement activation to the spontaneous deposition of C3 fragments and the formation of membrane attack complexes (MAC) on human B lymphocytes, were assessed by incubating peripheral blood mononuclear cells with autologous serum in the absence and presence of selective inhibitors of the AP and CP, respectively. While the total amount of C3 fragments deposited was relatively unaffected by blocking either pathway individually, deposition was virtually abrogated by their combined blockade. A marked difference was observed, however, in the nature of the fragments deposited as a result of CP and AP activation: C3b fragments deposited via the CP were extensively (∼ 90%) converted to the terminal degradation product, C3dg, whereas about 50% of those deposited by the AP persisted as C3b/iC3b fragments. The extent of MAC formation was also found to be highly pathway dependent, with the AP being about 15-fold more efficient at initiating this process than the CP. A model accounting for the effectiveness of the AP in both preserving C3 fragment integrity and initiating MAC is presented.